KIE Persiapan Calon Pengantin Dan Skrining Pranikah Di KUA Kecamatan Medan Johor Kota Medan Tahun 2023 - Edi Subroto; Cesy Marlianata Simanullang; Retno Wahyuni; Dewi Sartika Hutabarat; Mifta Hulzanah; Ester Simanullang (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The premarital period can be linked to the preconception period, because after marriage a woman will immediately undergo the conception process. The preconception period is the period before pregnancy. The preconception period is the period of time from three months to one year before conception and ideally should include the time when the ovum and sperm are mature, which is around 100 days before conception. The nutritional status of WUS or premarital women for three to six months during the preconception period will determine the condition of the baby born. The prerequisites for perfect nutrition during the preconception period are the key to the birth of a normal and healthy baby. Marriage is one of the steps that must be taken to build a harmonious family. To take this step, all preparations are needed to form a harmonious family. The goal after carrying out the activity is to hope that catin will be exposed to health material regarding pre-wedding preparation and pre-marital screening. KIE community service activities for catin preparation and premarital screening have been carried out in the form of counseling, providing information and education regarding catin preparation and premarital screening. With a commitment to providing KIE catin and program sustainability will be carried out by KUA Medan Johor. It is hoped that this activity will not end in service activities, but with the media leaflet it can be used as a policy for the relevant agencies to develop it in the form of an application as a course method for catin in the health sector so that KUAs in other areas can utilize the application in implementing courses for catin, especially in the field of health.